AOA Critical Issues: Dichotomies in Leadership. Presidential Address to the AOA, June 17, 2022. (4th January 2023) - Sebastianelli, Wayne J.
Abstract: This speech was given at the 2022 American Orthopaedic Association (AOA) meeting in Providence, Rhode Island, on June 17, 2022, and discusses the most important elements of leadership. A sense of extreme ownership is required for effective leadership. Ownership allows leaders to delegate responsibilities to others and to instill confidence and trust in the people closest to them. True leaders recognize that every situation creates value, regardless of the outcome, because each and every encounter is an opportunity to learn. Oftentimes, a situation creates a natural dichotomy or controversy. Good leaders must recognize this dichotomy and balance the decision-making that is required for such an occurrence for the ultimate good of the individual or organization. True leaders will include rather than exclude the people around them and will graduate the responsibilities of individuals as the skills and trust of those individuals develop. Those in charge must also recognize that leadership includes intelligence, compassion, and instinct. Leaders who are health-care providers must keep patient care as the true "North Star" so that appropriations of space, personnel, and finances are maximally utilized. Finally, true leaders achieve their goals through the core principles of balance, orchestration, growth, inclusion, and envision.